2022
DOI: 10.1158/1538-7445.am2022-ct009
|View full text |Cite
|
Sign up to set email alerts
|

Abstract CT009: Phase II trial of perioperative pembrolizumab plus capecitabine and oxaliplatin followed by adjuvant pembrolizumab for resectable gastric and gastroesophageal junction (GC/GEJ) adenocarcinoma

Abstract: Background: Perioperative therapy for locally advanced (LA) GC/GEJ adenocarcinoma is standard of care. Although immune checkpoint blockade (ICB) following chemoradiotherapy and resection significantly improves disease free survival (DFS) for esophageal cancer, the effectiveness of ICB together with chemotherapy in LA GC/GEJ cancer is unknown. Methods: This is a multicenter, single-arm, phase II clinical trial of pembrolizumab 200 mg every 3 weeks with capecitabine 625 mg/m2 twice daily and oxali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…The original search identified a total of 602 publications, and the study retrieval process is depicted in Figure 1. Twenty studies met the inclusion criteria, including a total number of 753 patients, were included in this meta-analysis (17,(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38). Of these, 15 studies reported that patients received neoadjuvant immunotherapy combined with chemotherapy, which our meta-analysis mainly focused on.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The original search identified a total of 602 publications, and the study retrieval process is depicted in Figure 1. Twenty studies met the inclusion criteria, including a total number of 753 patients, were included in this meta-analysis (17,(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38). Of these, 15 studies reported that patients received neoadjuvant immunotherapy combined with chemotherapy, which our meta-analysis mainly focused on.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Raufi et al. ( 54 ) reported that two of the three cases with grade 5 TRAEs among patients treated with pembrolizumab plus neoadjuvant CapeOX might attributable to treatment; no deaths were observed in the remaining patients during the dosing and perioperative period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21,22 However, only a few phase II studies investigated neoadjuvant ICIs combined with chemotherapy in LAGC and GEJC patients, with pCR rates ranging from 19.4% to 25.0%, and MPR rates ranging from 44.4% to 63.3%. [23][24][25][26][27][28] Besides, in the randomized phase IIb DANTE study, the pCR rate was 25% in patients received neoadjuvant atezolizumab plus FLOT regimen, 24% in the neoadjuvant FLOT group, whereas the MPR rates between these two groups were 49% and 44%, respectively. 26 Compared with these studies, our study presented a relatively lower pCR rate (10.3%), a higher MPR rate (69.0%), and improved safety profile.…”
Section: Discussionmentioning
confidence: 99%
“…In this phase II trial, 36 patients received 3 cycles of CAPOX + pembrolizumab (pembrolizumab 200 mg in combination with CAPOX every 3 weeks) before surgery as well as 3 cycles after surgery and 12 months pembrolizumab maintenance therapy. The primary endpoint could be reached with 20% pathological complete response (pCR) rate, and PFS and OS had not yet been reached [ 25 ]. However, grade 3 and greater adverse events were reported in more than half of the cohort, and 3 deaths occurred during the trial, 2 of which were possibly treatment-related.…”
Section: Gastric Adenocarcinomamentioning
confidence: 99%